OFF TO A GOOD START: ENHANCING READING SKILLS IN THAI CHILDREN (Proceedings of International Conference on Special Education, 2015)
This project, funded by the Australia Thailand Institute, is a collaborative project between Faculty of Education, Srinakharinwirot University, Thailand, and Faculty of Education and Social Work, University of Sydney, Australia, to promote reading skills in Thai children. Education is a fundamental human right. A key attribute in accessing an education is the skills of reading. Ensuring that a child has adequate reading skills allows the child to be able to learn independently from texts and other sources, to develop independent thinking, and to become a lifelong learner. This research project involved (1) examining the constructs that underpin learning to read in the Thailand language; (2) developing measures for assessing reading-related skills to monitor reading progresses in Thai primary students (i.e., onset awareness, non-word blending, non-word segmenting, letter knowledge, word reading, nonword reading, and passage reading measures); (3) developing a professional learning package for Thai teachers in develop a school-wide reading intervention model in their school; and (4) organizing workshops for teachers in order to introduce the instructional packages that focused instruction on key early skills. Twenty-Four teachers from the 12 public schools in Bangkok trialed the reading measures, participated in the workshops and field-tested the instructional packages. At the completion of the fieldwork teachers were interviewed to establish their understanding of the assessment tools, and instructional package. Results: The preliminary findings from the assessments and the interviews will be presented The data were examined in how they could assist teachers and schools to identify students at-risk in learning to read and interview data was used to establish how the instructional packages could be refined to better assist teachers use them in classrooms.